The Influence of Profitability, Liquidity, Leverage, and Firm Size on Financial Distress in Non-Food Retail (2021–2024) - Aisyah Amalia; Anna Sumaryati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purposes of this study analyze financial distress of non-food retail companies registered on the Indonesia Stock Exchange (IDX) between 2021 to 2024, as impacted by profitability, liquidity, leverage, and firm size. The sample criteria were as follows: (1) companies operating in the non-food retail sector and listed on the IDX during the specified period; (2) companies that consistently presented complete annual financial statements for each year; and (3) companies whose financial statements indicated that they reported a profit in the current year. Purposive sampling was employed to select the sample, resulting in 25 companies with a total of 100 observations. This research employed a quantitative approach using secondary data. The data were analyzed using multiple linear regression in SPSS version 25. The results of the partial test (t-test) revealed that profitability (ROA) and liquidity (CR) had a significant positive effect on financial distress. This suggests that higher profitability and liquidity increase the Altman Z-Score, thereby reducing the risk of a company experiencing financial distress. In contrast, leverage (DAR) and firm size (LN) were found to have no significant effect. These results emphasize the dominant role of internal factors, particularly profitability and liquidity, in shaping the financial condition of non-food retail companies in Indonesia.